How to cheat at deploying and securing RFID - Sanghera, Paul. (Rockland, Mass. : Syngress ; Oxford : Elsevier Science [distributor], 2007)
RFID is a method of remotely storing and receiving data using devices called RFID tags. RFID tags can be small adhesive stickers containing antennas that receive and respond to transmissions from RFID transmitters. RFID tags are used to identify and track everything from Exxon EZ pass to dogs to beer kegs to library books. For security professionals needing to get up and running fast with the topic of RFID, this How to Cheat approach to the topic is the perfect "just what you need to know" book! * For most business organizations, adopting RFID is a matter of when * The RFID services market is expected to reach $4 billion by 2008.
RFID Overview -- Security Breaches -- Hacking RFID -- Protecting the Supply Chain -- Modifying Product Information -- Protecting Personal Privacy.
Includes index.
Keywords: Radio frequency identification systems; Business logistics; Electronic books